Cambridge astronomy dictionary - Ridpath, Ian; Woodruff, John (Cambridge University Press, 1996)
Over 1000 clear and up-to-date entries, extensively cross-referenced. 50 diagrams and 30 tables. From aberration to zodiacal light, all the frequently used expressions are clearly defined. Brief biographies of over 100 famous astronomers (including Hale, Hawking, Holye and Hubble). Includes major observatories such as Palomar and Kitt Peak. A compact dictionary at an introductory level. Invaluable reference for active observers and armchair enthusiasts.